Tidal variability of phytoplankton and their environmental drivers in the freshwater reaches of the Guadiana estuary (SW Iberia) - Domingues, Rita B. (2012)
The effects of different phases of semidiurnal and spring-neap tidal cycles on phytoplankton and environmental drivers were evaluated in a tidal, freshwater location of a mesotidal estuary (Guadiana estuary, SW Iberia). An Eulerian approach was used and sampling covered different seasons during 2008. Samples were collected during spring and neap tides, at high tide, mid-ebb, low tide and mid-flood. Several physical-chemical variables were measured, as well as phytoplankton abundance and biomass. Salinity was higher at high-tide and suspended particulate matter was higher during spring tides and flood, due to higher vertical mixing and resuspension of bottom sediments. Chlorophyll a concentration during winter and summer neap tides was higher than during spring tides, whilst the abundance of pennate diatoms was higher during winter and Spring spring tides than during neap tides, probably reflecting differences in river discharge. Overall, tidally-induced differences detected in the freshwater tidal reaches of the Guadiana estuary were not as considerable as those observed in the lower estuary. However, the occurrence of tidally-induced variability in some seasons reflects that thorough sampling programs to study estuarine tidal dynamics should be conducted throughout the year. Occasional sampling will not reflect the typical variability of these highly dynamic systems.